2021
DOI: 10.1371/journal.pone.0249951
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a set of novel and robust 4-lncRNA-based nomogram predicting prostate cancer survival by bioinformatics analysis

Abstract: Background and objective Accumulating evidence shows that long noncoding RNAs (lncRNAs) possess great potential in the diagnosis and prognosis of prostate cancer (PCa). Therefore, this study aimed to construct an lncRNA-based signature to more accurately predict the prognosis of different PCa patients, so as to improve patient management and prognosis. Methods Through univariate and multivariate Cox regression analysis, this study constructed a 4 lncRNAs-based prognosis nomogram for the classification and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
(16 reference statements)
0
7
0
Order By: Relevance
“…Similarly, Zhangxiang et al identified PRRT3-AS1 as a potential biomarker of resistance to invasive treatment for breast carcinomas (24). Moreover, PRRT3-AS1 has also been reported as a part of prognostic models for glioblastoma (25), prostate cancer (26), hepatocellular carcinoma (27), and prostate cancer (28). These findings suggest that PRRT3-AS1 may be an oncogenic biomarker.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Similarly, Zhangxiang et al identified PRRT3-AS1 as a potential biomarker of resistance to invasive treatment for breast carcinomas (24). Moreover, PRRT3-AS1 has also been reported as a part of prognostic models for glioblastoma (25), prostate cancer (26), hepatocellular carcinoma (27), and prostate cancer (28). These findings suggest that PRRT3-AS1 may be an oncogenic biomarker.…”
Section: Discussionmentioning
confidence: 85%
“…Further, PRRT3-AS1 and AL031985.3 were identified as immune-related prognostic lncRNAs in HCC patients according to study from Liang R (25). Zhang P found that Five lncRNAs including PRRT3-AS1 were found related to focal adhesion, extracellular matrix receptor interaction, and mitogen-activated protein kinase signaling pathways in prostate cancer (26). Fan L also revealed silencing of lncRNA PRRT3-AS1 can upregulate apoptosis and autophagy downregulate migration and invasion of PC cells through the mTOR signaling pathway (28).…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, expressions of AC133961.1, LINC01679 and LINC02757 were found to be significantly increased in AML patients compared to healthy controls by qPCR assay. Among the 4 cuproptosis-related lncRNA signatures, LINC01679 was initially identified in a 4 lncRNAs-based prognostic model for classification and prediction of survival in patients with prostate cancer (PCa) (26). A study (27) investigated the role of LINC01679 in PCa and found that patients with low expressions of LINC01679 had worse survival outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…YEATS2-AS1 is differentially expressed in prostate cancer and is a high-risk factor for prostate cancer. 25 Zhang et al suggested that YEATS2-AS1 can be used as a biomarker to predict OS in sarcoma patients, providing new insights into the treatment of soft tissue sarcoma (STS). YEATS2-AS1 expression was found to be significantly higher in STS tissues than in normal tissues, and higher YEATS2-AS expression was associated with lower OS in STS patients.…”
Section: Discussionmentioning
confidence: 99%